Code-Switching Strategy in Efl in Speaking Ability (Lembaga Pengembangan Kinerja Dosen, 2025)
Mastery of English is one indicator of the readiness of the young generation to face global challenges, there are still many factors as students in mastering the English especially in speaking. Even EFL is taught since in the school to collage, the students still have trouble, the use of appropriate method should be applied to overcome the problem during teaching and learning EFL classroom by the teacher. The use of code-switching is the way to motivate the students in order to be active in speaking class. the aims of this study was to findout the use of Code switching strategy in EFL in speaking ability of students. In this study, there were 40 students of the midwifery study program and 3 English Lectures at STIK Bina Husada Palembang as study sample in the 2024/2025 academic year. The methodology used was mixed method and in collecting the data The instrument used were questionnaire that distributed to the midwifery students in second grade and Enlish lecturers in STIK Bina Husada and the speaking test was also given to the students as pre and post test. From the obtained results of the questionnaire showed that the students often used code-switching to explain the information more clearly, it can motivated them to be active event they were still trouble in limited of vocabulary and the English lecturers believed that code-switching in EFL class to help them conveyed the materials clearly to the students. And from the speaking test showed there were positive effect of this strategy to make students more in speaking that it can be seen from the development of students speaking in the class.